Over a barrel? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
In Madagascar questions have been asked in the leading periodical Dans les Médias Demain about what is to be done with the 10,000 barrels that carried the Fipronil insecticide that was widely used to fight the locust plagues of 1998 and 1999. Some...